Prevalence of self-medication in rural area of Andhra Pradesh - Gaurav M Rangari; Roza G Bhaisare; Venkatasandhya Korukonda; Y Lakshmi Chaitanya; N Hanumanth (Journal of Family Medicine and Primary Care, 2020)
Background: The consumption of medicine without consulting a doctor is called self-medication. In the recent decade, the prevalence of self-medication was increased mainly in the developing countries. The reason varies from the nonavailability of doctors to economical reason. But people are not aware of the side effects and interactions of drugs. This is risky behavior and may lead to death. The objective of this study is to find out the prevalence and various reasons, sources, and common drugs used for self-medication. Materials and Methods: A cross-sectional community-based study conducted in Visakhapatnam district, Andhra Pradesh. 166 houses were selected by using a simple random sampling method. One respondent from one household was interviewed by using a semi-structured questionnaire. The data obtained were analyzed by using SPSS V22. Chi-square and Fisher exact tests were applied to find associations. Phi, Cramer Rao V, and contingency coefficient were applied to find the strength of association. A value of P < 0.05 was considered significant. Results: Among 166 subjects, the majority (58.4%) of participants were in the age group between 18-30 and most of them were female 142 (85.5%). The prevalence of self-medication was 68.1%. The main source of self-medication was directly from the pharmacy, that is, pharmacists (72.6%). Analgesics were commonly (85%) self-medicated drug. The main indication for self-medication was headache (78.8%) and fever (66.4%). Conclusion: The prevalence of self-medication was high and which is hazardous to health. This needs prompt legislative action.